Enhancing Cognitive Development Through Playdough Media at Titian Sejaterah Kindergarten, Muaro Jambi Regency - Novita; Nita Priyanti (Yayasan pendidikan dzurriyatul Quran, 2025)
Early childhood education plays a strategic role in laying the foundation for cognitive, social, emotional, and motor development. However, initial observations at Titian Serjatera Kindergarten, Talang Pelita, revealed low cognitive abilities among children, with an average score of only 25% in the Not Yet Developed category. This study aimed to enhance children’s cognitive development through the use of playdough as a creative and interactive learning medium. The research employed a classroom action research (CAR) design based on Kurt Lewin’s model, consisting of planning, action, observation, and reflection stages, implemented over two cycles involving 15 children aged 5–6 years from group B. Data were collected using observation sheets for cognitive development and teacher performance, and analyzed quantitatively and qualitatively. The results indicated a significant improvement from an average score of 25% in the pre-action stage to 44.54% in Cycle I, and 75.56% in Cycle II, reflecting attainment of the Very Well Developed category. These findings demonstrate that the structured use of playdough effectively stimulates logical thinking, problem-solving, and creativity in young learners